Epidemiology, treatment and outcome of patients with lower respiratory tract infection presenting to emergency departments with dyspnoea (AANZDEMandEuroDEMstudies) - Rousseau, Geoffroy (WILEY, 2021)
10.1111/1742-6723.13567